Efeitos das mudanças climáticas sobre a diversidade de mamíferos não-voadores da Caatinga - Silva, Gibran Anderson Oliveira da (2022)
The Intergovernmental Panel on Climate Change predicts an increase of up to 4.8°C by 2100, with dryland regions becoming hotter and arider in the future. However, we know little about how these changes will affect species richness and composition patterns in the Caatinga, the largest threatened dry forest in South America. Here, we assessed how the non-volant mammal assemblages of the Caatinga would be affected by climate change. We used 20,461 occurrence records for 90 species to construct ecological niche models (ENMs) in a consensus model approach. Based on recently developed climate projections, we evaluate possible changes in the richness and beta diversity patterns of non-volant mammals for the years 2060 and 2100 under two Shared Socioeconomic Pathways scenarios: optimistic (SSP245) and pessimistic (SSP585) Between 77.6% and 90.6% of non-volant mammal species will lose suitable areas within the Caatinga and Neotropics especially small mammals associated with forest environments. At the community level, we project species loss for at least 75% of mammal communities by 2060. Local extinctions will be most significant in the extreme north and east of the Caatinga, bordering the Atlantic Forest. Half of the communities will undergo biotic homogenization by 2060, mainly in the lowlands. All in all, the contractions of suitable areas and loss of richness of mammal communities suggest that species currently live close to their ecological tolerances. The highly diffuse diversity-beta pattern raises alerts for the contemporary influence of anthropogenic disturbances that hinder the displacement and dispersal of mammals, especially in the northeastern and north-central Caatinga region. These chronic anthropogenic disturbances may interact with climate change and aggravate the loss of biodiversity in the Caatinga. Therefore, the use of forest mosaics that favor the permeability of landscapes between different topographic complexes is recommended. This reinforces the need for public-environmental policy planning and decision making to occur in an integrative manner between different administrative levels, to be effective for the conservation of Caatinga biodiversity a local and regional scale.